The effects of sleeping position, maternal smoking and substance misuse on the ventilatory response to hypoxia in the newborn period. (September 2018) - Rossor, Thomas; Ali, Kamal; Bhat, Ravindra; Trenear, Rebecca; Rafferty, Gerrard; Greenough, Anne
Abstract Background Maternal smoking, substance misuse in pregnancy and prone sleeping increase the risk of sudden infant death syndrome (SIDS). We examined the effect of maternal smoking, substance misuse and sleeping position on the newborn response to hypoxia. Methods Infants born between 36 and 42 weeks of gestational age underwent respiratory monitoring in the prone and supine sleeping position before and during a hypoxic challenge. Minute ventilation (MV) and end-tidal carbon dioxide (ETCO2 ) levels were assessed. Results Sixty-three infants were studied: 22 controls, 23 whose mothers smoked and 18 whose mothers substance-misused and smoked. In the supine position, baseline MV was higher and ETCO2 levels were lower in infants of substance-misusing mothers compared to controls (p = 0.015, p = 0.017, respectively). Infants of substance-misusing mothers had a lower baseline MV and higher ETCO2 levels in the prone position (p = 0.005, p = 0.004, respectively). When prone, the rate of decline in minute ventilation in response to hypoxia was greater in infants whose mothers substance-misused and smoked compared to controls (p = 0.002) and infants of smoking mothers (p = 0.016). Conclusion The altered response to hypoxia in the prone position of infants whose mothers substance-misused and smoked in pregnancy may explain their increased vulnerability to SIDS.